The Application of UTAUT Model To Understand The Purchase Intentions of Sayurbox During The COVID-19 Pandemic - Siroj Jibril Al Rasyidi; Prasetyo Hadi; Rosali Sembiring Colia (International Journal of Business Studies, 2022)
This study wants to analyze the effect of performance expectancy, effort expectancy and social influence of the Sayurbox application on their purchase intentions. This research was conducted quantitatively with the number of respondents being 100 Sayurbox consumers in Bekasi using Partial Least Square (PLS) analysis. The results of this study prove that performance expectancy and effort expectancy have a positive effect on purchase intentions, while social influence has no effect on consumer purchase intentions in Bekasi.